Velit outdoor final camp / Muhammad Nur Amin Salleh and Shahrir Fitri Shahrulzaman - Salleh, Muhammad Nur Amin; Shahrulzaman, Shahrir Fitri (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Outdoor Recreation Skills and Management course (SMG161), which is entirely focused on teaching and learning principles to produce high-caliber students, employs this program as a practical syllabus activity in the final evaluation. The framework of this program places an emphasis on techniques and skills for carrying out outdoor training or leisure activities, which is an educational concept extremely beneficial for human growth. The implementation of this program will give students the chance to expand their knowledge of outdoor recreational activities and make sure they have the necessary experience, abilities, and training. This is crucial because the students will eventually work in this field, either as part of their careers or as part of their industrial training. Practical outdoor recreation is defined as any sort of leisure time spent in a setting other than a classroom. This program concentrates on a variety of outdoor recreational activities, including kayaking, orienteering, navigation, trekking, living in nature, tying, and knotting, camping crafts, and rope activities. It is hoped that a program like this can promote students' high fighting spirit, integration, communication, and motivation.